Posztproduktivista átmenet? - avagy új funkciók a rurális térben - Szörényiné Kukorelli, Irén (Közép-Európai Közlemények, 2009)
After the transition in the ’90 years in the agricultural sector huge changes were played out concerning the land-privatization process. Insted of the state and cooperative property the private property was getting dominated. The restucturalisation of the economy touched not only the agrarium but the whole rural economy as well. The national parks and other protected areas generate more and more popular activities in the rural areas which link to the tourism activity in the northen-west part in Hungary and calls the attention to the role of diversified economy in the rural development in the changing Hungary.